101 PET-CT in patients with suspected paraneoplastic neurological conditions. Issue 12 (14th November 2019) - Cheema, Sanjay; Young, John; Pencharz, Deborah
Abstract : Background: PET-CT is often used to investigate for underlying malignancy in patients with suspected paraneoplastic neurological syndromes (PNS). However, evidence supporting its utility is limited, other than in patients with a 'classical' PNS, positive antibodies, and after conventional imaging has already been performed and is negative. Results: We collected data on 41 consecutive patients with suspected PNS who underwent whole-body PET-CT in our centre. 5/41 (12%) patients were antibody-positive. In 32/41 (78%) CT body imaging had been performed prior to PET-CT. In only one patient did PET-CT uncover a malignancy which was not already known about. In one patient PET-CT led to the diagnosis of neurosarcoidosis, which would not have been identified otherwise. No patients developed a malignancy in the follow up period (range: 10–33 months, median: 22 months) – a negative prediction value (NPV) of 100%. In 29% (12/41) PET-CT showed incidental findings which required further investigation or follow up. Conclusion: We found a low rate of detection of malignancy via PET-CT. This could be explained by low rates of antibody positivity and the small, heterogeneous cohort. The 100% NPV is reassuring. PET-CT identified a non-paraneoplastic condition (sarcoidosis) as a cause of one patient's symptoms.